Clitoria ternatea L. Extract as Adjuvant Therapy on Reducing IL–6 Levels in Reversal Reaction (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Reversal reaction is a type IV cellular hypersensitivity reaction in leprosy. Interleukin-6 is a mediator with a pleiotropic effect on inflammation and immune response. Steroids are the standard therapy in the treatment of reaction reversal. Clitoria ternatea flower extract has anti-inflammatory properties. Long-term use of steroids can cause side effects. Therefore, it is necessary to give adjuvant therapy that can shorten the treatment period. This study aims to analyze the effect of adjuvant therapy of Clitoria ternatea extract to reduce IL-6 levels in reversal reaction. Experimental research design with pre and post-randomized single-blinded controlled trial, involving 22 subjects with reversal reaction. The control group received standard therapy and the treatment group received standard and adjuvant therapy with Clitoria ternatea extract. IL-6 levels were measured by ELISA. Data analysis used the Wilcoxon test and Independent T-test. The results showed a significant difference in treatment group (p=0.003) and control group (p=0.016). The mean decrease in serum IL-6 levels in treatment group was 81.35 pg/ml and in control group was 24.30 pg/ml (p=0.027). Clitoria ternatea showed a significant IL-6-lowering effect in patients with reversal reactions. This study has demonstrated the potential of Clitoria ternatea extract as adjuvant therapy in patients with leprosy reactions.